(untitled) (Journal of Applied Membrane Science & Technology, 2017)
The demand of bio–ethanol to substitute petroleum–based fuel is continuously increasing, and economic aspect has become an important factor in the design of ethanol dehydration plants. Since it forms an azeotrope at 89.4 mole%, 78°C and atmospheric pressure, further dehydration process is difficult and expensive. In this work, a composite membrane using modified poly vinyl alcohol (PVA) as the active separating layer, and poly–acrylonitrite (PAN) as a supportive layer was employed. Two membrane processes, pervaporation (PV) and vapor permeation (VP) system, were investigated for their dehydration performances in order to produce motor fuel grade ethanol (MFGE). The effects of feed temperature, feed pressure, feed composition, module temperature, and permeate pressure were compared for both systems, and also discussed in detail. Total flux, ethanol flux, and water flux as well as separation factor were also calculated. In general for both systems, the water fluxes decreased dramatically as the feed side ethanol concentrations increased. However, the pervaporation system was affected the most, and this is because of the low diffusivity of water in ethanol. For the separation of azeotrope, water fluxes between 0.06–1.17 kg/m2/hr with separation factor of about 100 were observed in VP whilst the value of 0.10–0.22 kg/m2/hr were obtained with PV. In conclusion, VP has advantages over PV system in terms of separation performances and simplicities of the process.